2017
DOI: 10.1038/s41522-017-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards individualized diagnostics of biofilm-associated infections: a case study

Abstract: Organized within biofilm communities, bacteria exhibit resistance towards a broad spectrum of antibiotics. Thus, one might argue that bacteria isolated from biofilm-associated chronic infections should be subjected to resistance profiling under biofilm growth conditions. Various test systems have been developed to determine the biofilm-associated resistance; however, it is not clear to what extent the in vitro results reflect the situation in vivo, and whether the biofilm-resistance profile should guide clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
18
0
4
Order By: Relevance
“…The more efficient an antimicrobial therapy is, the more space it leaves for surviving bacteria to repopulate the empty niche. A similar fast repopulation of the biofilms might be the reason why in the clinic colistin treatment, despite being more effective in killing of biofilm cells (demonstrated here and before [37]), is not superior to an inhalative therapy with tobramycin (55-57). One might even argue that repeated killing and fast regrowth of the bacteria leave bacterial debris that may trigger a strong inflammatory response contributing to tissue destruction.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The more efficient an antimicrobial therapy is, the more space it leaves for surviving bacteria to repopulate the empty niche. A similar fast repopulation of the biofilms might be the reason why in the clinic colistin treatment, despite being more effective in killing of biofilm cells (demonstrated here and before [37]), is not superior to an inhalative therapy with tobramycin (55-57). One might even argue that repeated killing and fast regrowth of the bacteria leave bacterial debris that may trigger a strong inflammatory response contributing to tissue destruction.…”
Section: Discussionmentioning
confidence: 74%
“…We tested colistin, which disrupts the outer membrane, and tobramycin, a well-known translational inhibitor. The biofilms were allowed to establish in flow chambers under continuous-flow conditions, and the antibiotic activity was monitored by following uptake of propidium iodide (PI), which is not permeant to live cells and thus has proved to be a reliable indicator of cell death (37)(38)(39)(40). For Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that clinical P. aeruginosa isolates from various patients and infectious sites exhibit very different in vitro biofilm structures. 40,41 In this study, we recorded the biofilm phenotypes of 414 clinical P. aeruginosa isolates by the use of confocal laser scanning microscopy (CLSM) following live/dead staining. Clinical isolates exhibited a large diversity of biofilm phenotypes; however, on the basis of visual inspection of microscopy images, we identified clusters of strains that share common structural characteristics (Fig.…”
Section: Biofilm Phenotypes Of Clinical P Aeruginosa Isolates Fall Imentioning
confidence: 99%
“…There is a drastic increase in antibiotic tolerance using biofilm-based diagnostics, such as the Calgary device, in comparison to MIC methods, demonstrating the limitation of using planktonic-based models for biofilm infections [7]. Some of these in vitro biofilm models are robust for antibiotic susceptibility screening; they fail to recapitulate the complexity of biofilm infections, environment and host-dependent interactions [6, 8], all of which affect the antibiotic susceptibility profile [8]. Also, these biofilm models have not been developed to demonstrate antibiotic susceptibility profile in multi-species infections.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these biofilm models have not been developed to demonstrate antibiotic susceptibility profile in multi-species infections. Thus, if diagnostic tests fail to accurately detect in vivo antibiotic resistance, this will result in in recurrent and complicated infections [8], and may lead to a vicious cycle of increased resistance.…”
Section: Introductionmentioning
confidence: 99%